The future objectives of the International Mouse Phenotyping Consortium (IMPC): functional evaluation of human disease-relevant cis-regulatory elements in the mouse genome - Naoki Kubo; Akiko Oguchi; Hiroshi Masuya; Takanori Amano; Akihiko Sakashita; Hideya Kawaji; Takeya Kasukawa; Shinya Oki; Shinya Ayabe; Toyoyuki Takada; Atsuo Ogura; Kimiko Inoue; et al. (Mammalian Genome, 2026)
The International Mouse Phenotyping Consortium (IMPC) has established a large-scale functional genomics resource by systematically generating and phenotyping knockout mouse lines, linking gene function to mammalian phenotypes. However, interpreting disease-associated non-coding variants remains particularly challenging due to their abundance, context-dependent activity, and the complexity of gene regulation. Genome-wide association studies (GWAS) have shown that many disease-associated loci map to non-coding regions. In addition, recent large-scale consortia have catalogued millions of candidate cis-regulatory elements (CREs) across mammalian genomes; however, predicting which elements contribute to disease-relevant gene regulation and organismal phenotypes remains difficult. Together, these observations highlight disease-relevant CREs as an important but still underexplored component of human disease mechanisms. In this white paper, we outline strategies to address this challenge: (i) prioritization of disease-relevant candidate CREs, (ii) genome editing in mice to functionally evaluate CREs, and (iii) the establishment of interdisciplinary working groups. By extending its activities beyond protein-coding sequences, the IMPC has a unique opportunity to define the functional and phenotypic impact of disease-relevant CREs in vivo at scale, thereby improving our understanding of how non-coding regulatory elements contribute to mammalian phenotypes and human disease.

Development of 5-year risk prediction models for incident dementia and mortality in a community-dwelling older Japanese population: The Japan Prospective Studies Collaboration for Aging and Dementia (JPSC‐AD) - Xiangyin Meng; Takanori Honda; Tomoyuki Ohara; Yoshihiko Furuta; Mao Shibata; Jun Hata; Yasuyuki Taki; Tatsuya Mikami; Tetsuya Maeda; Kenjiro Ono; Masaru Mimura; Ritsuko Hanajima; et al. (GeroScience, 2026)
Improving cognitively healthy survival is important for achieving healthy aging. Therefore, it would be valuable to estimate the future risk of either incident dementia or death in community-dwelling older adults. This study aimed to develop a set of risk prediction models for either incident dementia or death that can be applied according to data availability across diverse clinical settings, using longitudinal data from community-dwelling older Japanese adults. A total of 8,334 participants aged ≥65 years were prospectively followed up from 2016 to 2023. Logistic regression was used to develop multivariable prediction models. The developed models were translated into simplified scoring systems based on the β coefficients. The discrimination abilities of the models were assessed by C-statistics, and the calibration was assessed by calibration plots. During the follow-up period, 1,151 participants developed either dementia or death. In the multivariable model using potential predictors commonly available in the primary care setting, age, male sex, formal education ≤9 years, diabetes mellitus, use of lipid-lowering agents, leanness, history of stroke, history of heart disease, history of respiratory disease, history of cancer, current smoking, no regular exercise habit, and low frequency of social interactions were selected as predictors. Adding cognitive status, depressive symptoms, apolipoprotein E-ε4 carrier status, and brain MRI markers to the model further enhanced its predictive performance. The developed models and simplified scores showed good discrimination and calibration. Risk stratification with our models may be useful for assessing the risks of incident dementia and death and, consequently, for prolonging cognitively healthy survival.

Jasminumosides F–K, oligomeric secoiridoid glycosides from jasmin: the flowers of Jasminum sambac (L.) Aiton - Naoki Inoue; Yoshiaki Manse; Toshio Morikawa (Journal of Natural Medicines, 2026)

Impact of Postnatal Changes in Creatinine Levels on Plasma Gentamicin Concentrations in Neonates - Haruka Tsushita; Ryota Tanaka; Masanori Inoue; Ryosuke Tatsuta; Shintaro Kishimoto; Tomoki Maeda; Naoki Yoshikawa; Kenji Ihara; Hiroki Itoh (Pharmaceutical Research, 2026)

Irrigation with ABA Solution Induces the Accumulation of Pyrethrin II in Seedlings of Pyrethrum (Tanacetum cinerariifolium) - Kisumi Takiguchi; Shiro Inoue; Kazuhiko Matsuda; Naoki Kitaoka; Hideyuki Matsuura (Journal of Plant Growth Regulation, 2026)

Comparison of Predatory Phenotypes and Genotypes Between Bdellovibrio sp. BIS2 and Bacteriovorax sp. HI3 Isolated From the Same Freshwater Environment - Tomomi Sugiyama; Tsubasa Kojima; Naoki A. Uemura; Daisuke Nakane; Hideo Dohra; Daisuke Inoue; Michihiko Ike (Environmental Microbiology, 2026)
Bdellovibrio and like organisms (BALOs) are predatory bacteria, which play crucial roles in shaping community structure and maintaining diversity in microbial ecosystems. However, functional and genetic variation among coexisting BALOs remains largely unexplored. Here, we characterised Bdellovibrio sp. BIS2 and Bacteriovorax sp. HI3, which were isolated from the same freshwater environment at different time points. Predation assays and a functional genomic analysis revealed that the predators have distinct prey ranges and predatory behaviours with associated genotypic differences, which may contribute to niche partitioning in the shared habitat. BIS2 possessed an extensive set of flagellar genes, likely contributing to its higher motility and rapid spatial exploration. However, cell debris remained after predation because the prey cells were incompletely lysed. HI3 displayed efficient localised predation and thorough lysis of prey cellular components. The difference in predation efficiency was likely attributed to distinct profiles of hydrolytic enzymes in the two BALOs, including enzymes critical for prey cell lysis and exit from the prey. Genomic regions unique to each predator with predation‐associated genes suggest that genetic divergence drove the evolution of specialised predatory properties across BALOs. These findings provide insights into variation in predatory traits among BALOs, a key mechanism enabling coexistence and adaptation.

Detection of three novel loci involved in reduced seed-shattering behaviour of an aus rice cultivar, Oryza sativa Kasalath - Naoki Shionari; Yudai Yamaguchi; Natsumi Takama; Yumi Oka; Yoshiaki Takenaka; Naohiro Matsubara; Chizuru Inoue; Than Myint Htun; Yuki Tsujimura; Koji Numaguchi; Takashige Ishii; Ryo Ishikawa (Molecular Genetics and Genomics, 2025)

Oligomeric secoiridoid glycosides with hepatoprotective activity from the flowers of Jasminum sambac (L.) Aiton - Naoki Inoue; Yusuke Sakamoto; Yoshiaki Manse; Kiyofumi Ninomiya; Toshio Morikawa (Phytochemistry, 2025)

From the plate to the brain: associations between dietary patterns and reduced dementia prevalence and white matter lesions in older Japanese adults - Liying Chen; Yasuko Tatewaki; Benjamin Thyreau; Kazuhiro Uchida; Hikari Iki; Shigeyuki Nakaji; Tetsuya Maeda; Kenjiro Ono; Moeko Noguchi-Shinohara; Masaru Mimura; Kenji Nakashima; Jun-ichi Iga; et al. (GeroScience, 2025)
Diet is widely considered essential in dementia, but its association with white matter lesions (WMLs) remains unclear. This cross-sectional study investigated the associations between dietary patterns, dementia, and WMLs in a large, nationwide, multicenter population of older Japanese adults. A total of 8,938 adults (aged ≥ 65; 73 ± 6.3 years old) from the Japan Prospective Studies Collaboration for Aging and Dementia (JPSC-AD) were included. Dietary intake was assessed using a Food Frequency Questionnaire. Principal component analysis was used to derive dietary patterns. A trained Convolutional Neural Network model segmented WMLs from brain MR images. Logistic regression estimated odds ratios (ORs) for dementia by dietary pattern quartiles, while linear regression assessed associations with WML volumes. Five dietary patterns were extracted. A Japanese diet including protein and minerals was significantly associated with lower prevalence of all-cause dementia (OR = 0.56) and Alzheimer’s disease (OR = 0.47), and with reduced WML volume ( β = − 0.03). Similar directional trends in ORs were observed across study sites. The reverse association with WMLs remained significant among individuals without dementia, reducing the likelihood of reverse causation. A Japanese diet including protein and minerals was associated with lower dementia prevalence and smaller WML volume in older Japanese adults. Drawing on nationwide, large-scale, multicenter data, these findings advance our understanding of dietary patterns in older Japanese adults and provide valuable insights for future intervention studies targeting diet and age-related brain changes.

Distribution of evergreen broad-leaved forests, inferred from phytolith, in the southernmost area of the Japanese Archipelago between the terminal Pleistocene and early Holocene - Naoki Hayashi; Jun Inoue (Quaternary International, 2025)

DO Toxic Invasive Prey Become a Toxin Source for Native Consumers? - Kiyoto Sawada; Takato Inoue; Naoki Mori; Akira Mori; Takashi Kamijo (Journal of Chemical Ecology, 2024)

Alkylphthalides with intracellular triglyceride metabolism-promoting activity from the rhizomes of Cnidium officinale Makino - Toshio Morikawa; Naoki Inoue; Saya Yamamoto; Miyuki Shiotani; Yoshiaki Manse; Kiyofumi Ninomiya (Journal of Natural Medicines, 2024)

Intrinsic Factors Associated with Dietary Toxin Quantity and Concentration in the Nuchal Glands of a Natricine Snake Rhabdophis Tigrinus - Takato Inoue; Akira Mori; Naoko Yoshinaga; Naoki Mori (Journal of Chemical Ecology, 2023)

Ursane-type triterpene oligoglycosides with anti-hepatosteatosis and anti-hyperlipidemic activity from the leaves of Ilex paraguariensis A. St.-Hil. - Akifumi Nagatomo; Naoki Inoue; Takuya Konno; Yin Xu; Chinatsu Sakamoto; Mayuko Sone; Aya Shibasaka; Osamu Muraoka; Kiyofumi Ninomiya; Masayuki Yoshikawa; Yoshiaki Manse; Toshio Morikawa (Journal of Natural Medicines, 2022)

New Insights Into Dietary Toxin Metabolism: Diversity in the Ability of the Natricine Snake Rhabdophis tigrinus to Convert Toad-Derived Bufadienolides - Takato Inoue; Ryu Nakata; Alan H. Savitzky; Naoko Yoshinaga; Akira Mori; Naoki Mori (Journal of Chemical Ecology, 2021)

Variation in Bufadienolide Composition of Parotoid Gland Secretion From Three Taxa of Japanese Toads - Takato Inoue; Ryu Nakata; Alan H. Savitzky; Naoko Yoshinaga; Akira Mori; Naoki Mori (Journal of Chemical Ecology, 2020)

Effects of Dietary Supplementation with Fish Scales-Derived Collagen Peptides on Skin Parameters and Condition: A Randomized, Placebo-Controlled, Double-Blind Study - Seiko Koizumi; Naoki Inoue; Maiko Shimizu; Chang-ju Kwon; Hwa-young Kim; Kyoung Sik Park (International Journal of Peptide Research and Therapeutics, 2018)

Effects of time and environmental conditions on the quality of DNA extracted from fecal samples for genotyping of wild deer in a warm temperate broad-leaved forest - Yoshimi Agetsuma-Yanagihara; Eiji Inoue; Naoki Agetsuma (Mammal Research, 2017)

Different acute toxicity of fipronil baits on invasive Linepithema humile supercolonies and some non-target ground arthropods - Daisuke Hayasaka; Naoki Kuwayama; Azuma Takeo; Takanobu Ishida; Hiroyuki Mano; Maki N. Inoue; Takashi Nagai; Francisco Sánchez-Bayo; Koichi Goka; Takuo Sawahata (Ecotoxicology, 2015)

Gibberella ear rot of corn caused by Fusarium asiaticum in Japan - Akira Kawakami; Naoki Kato; Takahide Sasaya; Keisuke Tomioka; Hiroyoshi Inoue; Atsushi Miyasaka; Kazuyuki Hirayae (Journal of General Plant Pathology, 2015)

Microbiome/microbiota and allergies - Yuzaburo Inoue; Naoki Shimojo (Seminars in Immunopathology, 2015)

Simultaneous determination of water-soluble vitamins in beverages and dietary supplements by LC-MS/MS - Ayano Kakitani; Tomonori Inoue; Keiko Matsumoto; Jun Watanabe; Yasushi Nagatomi; Naoki Mochizuki (Food Additives & Contaminants: Part A, 2014)

Exchange and Complementation of Genes Coding for Photosynthetic Reaction Center Core Subunits among Purple Bacteria - Kenji V. P. Nagashima; André Verméglio; Naoki Fusada; Sakiko Nagashima; Keizo Shimada; Kazuhito Inoue (Journal of Molecular Evolution, 2014)

Down-regulation of miR-124/-214 in cutaneous squamous cell carcinoma mediates abnormal cell proliferation via the induction of ERK - Keitaro Yamane; Masatoshi Jinnin; Tomomi Etoh; Yuki Kobayashi; Naoki Shimozono; Satoshi Fukushima; Shinichi Masuguchi; Keishi Maruo; Yuji Inoue; Tsuyoshi Ishihara; Jun Aoi; Yuichi Oike; et al. (Journal of Molecular Medicine, 2013)

Comparison of Bioconcentration and Biomagnification Factors for Poorly Water-Soluble Chemicals Using Common Carp (Cyprinus carpio L.) - Yoshiyuki Inoue; Naoki Hashizume; Tomohiko Yoshida; Hidekazu Murakami; Yasuyuki Suzuki; Yuka Koga; Ryoko Takeshige; Erina Kikushima; Naoaki Yakata; Masanori Otsuka (Archives of Environmental Contamination and Toxicology, 2012)

Unique Physicochemical Properties of Perfluorinated Compounds and Their Bioconcentration in Common Carp Cyprinus carpio L. - Yoshiyuki Inoue; Naoki Hashizume; Naoaki Yakata; Hidekazu Murakami; Yasuyuki Suzuki; Erina Kikushima; Masanori Otsuka (Archives of Environmental Contamination and Toxicology, 2012)

Comparison of Nitrofen Uptake via Water and Food and its Distribution in Tissue of Common Carp, Cyprinus carpio L. - Yoshiyuki Inoue; Naoki Hashizume; Erina Kikushima; Masanori Otsuka (Bulletin of Environmental Contamination and Toxicology, 2011)

Life stage-related differences in susceptibility to acrylamide-induced neural and testicular toxicity - Miwa Takahashi; Kaoru Inoue; Naoki Koyama; Midori Yoshida; Kaoru Irie; Tomomi Morikawa; Makoto Shibutani; Masamitsu Honma; Akiyoshi Nishikawa (Archives of Toxicology, 2011)

Fine-scale spatial structure of genets and sexes in the dioecious plant Dioscorea japonica, which disperses by both bulbils and seeds - Inoue Mizuki; Kiyoshi Ishida; Naoki Tani; Yoshihiko Tsumura (Evolutionary Ecology, 2010)

An overview on chlorophylls and quinones in the photosystem I-type reaction centers - Shunsuke Ohashi; Tatsuya Iemura; Naoki Okada; Shingo Itoh; Hayato Furukawa; Masaaki Okuda; Mayumi Ohnishi-Kameyama; Takuro Ogawa; Hideaki Miyashita; Tadashi Watanabe; Shigeru Itoh; Hirozo Oh-oka; et al. (Photosynthesis Research, 2010)

Fluorescence Lymph Node Mapping in Living Mice Using Quantum Dots and a Compression Technique - Yusuke Inoue; Shigeru Kiryu; Makoto Watanabe; Naoki Oyaizu; Kuni Ohtomo (Journal of Fluorescence, 2010)

A novel membrane-anchored cytochrome c-550 of alkaliphilic Bacillus clarkii K24-1U: expression, molecular features and properties of redox potential - Shinichi Ogami; Shoichi Hijikata; Tamotsu Tsukahara; Yasuhiro Mie; Toshihide Matsuno; Naoki Morita; Isao Hara; Koji Yamazaki; Norio Inoue; Atsushi Yokota; Tamotsu Hoshino; Kazuaki Yoshimune; et al. (Extremophiles, 2009)

Genetic variations in the gB, UL144 and UL149 genes of human cytomegalovirus strains collected from congenitally and postnatally infected Japanese children - Hainian Yan; Shin Koyano; Yuhki Inami; Yumiko Yamamoto; Tatsuo Suzutani; Masashi Mizuguchi; Hiroshi Ushijima; Ichiro Kurane; Naoki Inoue (Archives of Virology, 2008)

Extracellular matrix of Magnaporthe oryzae may have a role in host adhesion during fungal penetration and is digested by matrix metalloproteinases - Kanako Inoue; Tomoko Suzuki; Kenichi Ikeda; Shan Jiang; Naoki Hosogi; Gang-Su Hyon; Sizuka Hida; Taku Yamada; Pyoyun Park (Journal of General Plant Pathology, 2008)

Extracellular matrix of Magnaporthe oryzae may have a role in host adhesion during fungal penetration and is digested by matrix metalloproteinases - Kanako Inoue; Tomoko Suzuki; Kenichi Ikeda; Shan Jiang; Naoki Hosogi; Gang-Su Hyong; Sizuka Hida; Taku Yamada; Pyoyun Park (Journal of General Plant Pathology, 2007)

Binding of tetrakis(pyrazoliumyl)porphyrin and its copper(II) and zinc(II) complexes to poly(dG-dC)2 and poly(dA-dT)2 - Daryono H. Tjahjono; Rahmana E. Kartasasmita; As’ari Nawawi; Shunsuke Mima; Takehiro Akutsu; Naoki Yoshioka; Hidenari Inoue (JBIC Journal of Biological Inorganic Chemistry, 2006)

Reactive oxygen species (ROS) generation and ROS-induced lipid peroxidation are associated with plasma membrane modifications in host cells in response to AK-toxin I from Alternaria alternata Japanese pear pathotype - Naoto Shimizu; Naoki Hosogi; Gang-Su Hyon; Shan Jiang; Kanako Inoue; Pyoyun Park (Journal of General Plant Pathology, 2006)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Senescence marker protein-30 (SMP30) induces formation of microvilli and bile canaliculi in Hep G2 cells - Akihito Ishigami; Toshiko Fujita; Haruhiko Inoue; Setsuko Handa; Sachiho Kubo; Yoshitaka Kondo; Naoki Maruyama (Cell and Tissue Research, 2005)

Metabolic activities of partially degenerated hypertrophic chondrocytes: gene expression of hyaluronan synthases - Yuki Takada; Hisako Sakiyama; Kazuko Kuriiwa; Riako Masuda; Naokazu Inoue; Koichi Nakagawa; Naoki Itano; Toshiyuki Saito; Takeshi Yamada; Koji Kimata (Cell and Tissue Research, 1999)

Lack of biliary excretion of Cd linked to an inherent defect of the canalicular isoform of multidrug resistance protein (cMrp) does not abnormally stimulate accumulation of Cd in the Eisai hyperbilirubinemic (EHB) rat liver - Naoki Sugawara; Koji Arizono; Toshiichi Kitajima; Hideaki Inoue; Yu-Rong Lai (Archives of Toxicology, 1997)